Respuesta :
(3u+3)-(3u+3)
3u+3-3u-3
3u-3u+3-3
0+0
(3u+3)-(3u+3)=0
Hope I didn't mess up for your sake
3u+3-3u-3
3u-3u+3-3
0+0
(3u+3)-(3u+3)=0
Hope I didn't mess up for your sake
Answer: 0
Step-by-step explanation:
The given expression : [tex](3u+3)-(3u+3)[/tex]
Now to subtract one impression from other , we first open parenthesis and multiply (-) negative sign to inside it , we get
[tex]3u+3-3u-3\\\\=3u-3u+3-3[/tex]
Combine like terms , we get
[tex]0+0=0[/tex]
Hence, the required answer is 0.
Thus , [tex](3u+3)-(3u+3)=0[/tex]